Analysis the Role of Ahlussunnah Wal Jama'ah through PMII on Economic Development in Regional Planning in Medan City - Ratno Afandi; Suwardi Lubis; Linda Trimurni Maas (LPPPIPublishing, 2022)
The purpose of this study is to provide an overview regarding the role of PMII Medan city branch in economic development. The movement carried out by PMII in economic development is to instill Ahlussunnah Wal Jamaah values ??as Manhaj al fikr, with the principles of tawasuth (moderate), tawazun (neutral), ta'adul (balance), and tasamuh (tolerant) in building a movement towards development economy by building a balanced economic system between the position of the State, market and society, especially in the city of Medan. Based on the research results, all PMII activities, both informal and non-formal, as well as the economic development institutions initiated by the Medan branch of the PMII have stimulation and have a positive effect on economic development in the city of Medan.